2022
DOI: 10.3390/geographies2010006
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Change of Land Cover in Protected Areas in Malawi: Implications for Conservation Management

Abstract: Protected areas (PAs) transform over time due to natural and anthropogenic processes, resulting in the loss of biodiversity and ecosystem services. As current and projected climatic trends are poised to pressurize the sustainability of PAs, analyses of the existing perturbations are crucial for providing valuable insights that will facilitate conservation management. In this study, land cover change, landscape characteristics, and spatiotemporal patterns of the vegetation intensity in the Kasungu National Park… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 95 publications
4
3
0
Order By: Relevance
“…Our result confrms with the previous study of the authors in [51] that LCC from forest to shrub conversion was the main form of land cover transition observed in the Kasungu National Park of Malawi. In contrast to the current fndings, the study was conducted by the authors in [59] in Awash National Park and the grassland was expanded by 14.2% between 1972 and 1986 as well as by 10.5% of the study area during the entire study period .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our result confrms with the previous study of the authors in [51] that LCC from forest to shrub conversion was the main form of land cover transition observed in the Kasungu National Park of Malawi. In contrast to the current fndings, the study was conducted by the authors in [59] in Awash National Park and the grassland was expanded by 14.2% between 1972 and 1986 as well as by 10.5% of the study area during the entire study period .…”
Section: Discussionsupporting
confidence: 92%
“…Te results of the classifcation produced were acceptable accuracies (Table 7) and are generally compatible with prior studies involving Landsat image classifcation [51]. We identifed various land cover patterns in HAPNP after analyzing the change in land cover between 1990 and 2021.…”
Section: Discussionsupporting
confidence: 84%
“…These findings broadly corroborate the findings of Kpienbaareh et al ( 2022 ) and Palamuleni et al ( 2007 ) who demonstrated that the close association of LULC classes often leads to mixed pixels, particularly in savanna landscapes where habitats are spatially clustered and scattered and have gradual boundaries. Thus, in addition to Clinton et al ( 2010 ), who reported that classification inaccuracy is a resultant of poor classifier and/or poor segmentation, this study suggests that classification accuracy is also affected by spatial patterns in habitat (LULC) distribution.…”
Section: Discussionsupporting
confidence: 91%
“…Since 1990, these habitats have undergone significant degradation, mainly because of encroachment and deforestation (Bone et al, 2017 ; Kalipeni, 1992 ; Mawenda et al, 2020 ; Zulu, 2010 ). However, from 2015 onwards, the conservation areas have been undergoing restoration (Bone et al, 2017 ; Kpienbaareh et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation